Characterization of Management based on Semantic Technologies for the Administration of Computer Networks (Ciencias de la Ingeniería y Aplicadas, 2018)
The multiple computer network management models (SNMP, CMIP, DMI, WBEM) raise the need to define several mechanisms that allow interoperability between all network management domains involved. The basic component of these interoperabilities is the correspondence between the information models that each domain specifies. These maps, which are usually carried out with syntactic translations, can reach the semantic level through the use of ontologies. This article aims to show the advantages of the use and application of formal ontology techniques in order to improve the integration of current network management models. The application of this information for network management, independent of the specific management model that may interact with the managed resources, may also include basic behavioral constraints.
Keywords: Managers; Domain; Ontology; Model; Interoperability; Semantics; Behaviors; Integration; OWL; CIM